The Effect Of Company Size, Roe, and Der On Company Value In The Property And Real Estate Sector Listed On The IDX - Putri Nur Atikah; Jumeida Simatupang (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This research aims to determine the influence of company size, Return On Equity, and Debt to Equity Ratio on company value in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2019 - 2022. The method in this research is a quantitative method, namely analyzing and testing data using numbers with descriptive statistical test tools, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination tests. Research Results: firm size partially has no negative but significant effect on firm value, Return On Equity partially has a negative and significant effect on firm value, Debt to Equity Ratio partially has no effect but significant on firm value, the firm size, Return On Equity, and Debt to Equity Ratio simultaneously and significantly influence firm value.